The effect of using an auxiliary device in teaching the spindle skill on the pommel horse in the artistic gymnastics for juniors - Jamal, Abdulaa; Muayed, Ghada (Journal of Physical Education, 2023)
The research aimed to indentify the effect of using an auxiliary device in teaching the skill of the spindle on the pommel horse apparatus. The research hypothesized that the use of the auxiliary device has a positive effect in teaching the skill of the spindle on the pommel horse apparatus. The researchers used the experimental approach in one group design with pre post-test. The research sample consisted of (6) players o from the Iraqi national team for gymnastics with ages (9-13) years. The researchers concluded that the use of the assistive device had a positive effect in teaching the spindle skill on the pommel horse, and recommended the need to use the assistive device in teaching other skills on the pommel horse.